Melphalan induces cardiotoxicity through oxidative stress in cardiomyocytes derived from human induced pluripotent stem cells - Rui Liu; Dong Li; Fangxu Sun; Antonio Rampoldi; Joshua T. Maxwell; Ronghu Wu; Peter Fischbach; Sharon M. Castellino; Yuhong Du; Haian Fu; Anant Mandawat; Chunhui Xu (Stem Cell Research & Therapy, 2020)
Abstract Background Treatment-induced cardiotoxicity is a leading noncancer-related cause of acute and late onset morbidity and mortality in cancer patients on antineoplastic drugs such as melphalan—increasing clinical case reports have documented that it could induce cardiotoxicity including severe arrhythmias and heart failure. As the mechanism by which melphalan impairs cardiac cells remains poorly understood, here, we aimed to use cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CMs) to investigate the cellular and molecular mechanisms of melphalan-induced cardiotoxicity. Methods hiPSC-CMs were generated and treated with clinically relevant doses of melphalan. To characterize melphalan-induced cardiotoxicity, cell viability and apoptosis were quantified at various treatment durations. Ca2+ transient and contractility analyses were used to examine the alterations of hiPSC-CM function. Proteomic analysis, reactive oxygen species detection, and RNA-Sequencing were conducted to investigate underlying mechanisms. Results Melphalan treatment of hiPSC-CMs induced oxidative stress, caused Ca2+ handling defects and dysfunctional contractility, altered global transcriptomic and proteomic profiles, and resulted in apoptosis and cell death. The antioxidant N-acetyl-l-cysteine attenuated these genomic, cellular, and functional alterations. In addition, several other signaling pathways including the p53 and transforming growth factor-β signaling pathways were also implicated in melphalan-induced cardiotoxicity according to the proteomic and transcriptomic analyses. Conclusions Melphalan induces cardiotoxicity through the oxidative stress pathway. This study provides a unique resource of the global transcriptomic and proteomic datasets for melphalan-induced cardiotoxicity and can potentially open up new clinical mechanism-based targets to prevent and treat melphalan-induced cardiotoxicity.